Causal ambiguity: deciphering the etiology of secondary thrombotic microangiopathy with systemic lupus erythematosus and vivax malaria - Soni, Jinal R.; Garg, Ambuj; Aggarwal, Pankaj; Gupta, Anurag; Gupta, Pallav (International Journal of Research in Medical Sciences, 2023)
Hemolytic uremic syndrome (HUS) falls under the spectrum of thrombotic microangiopathy (TMA) characterized by microangiopathic hemolytic anemia, thrombocytopenia, and thrombi in small vessels leading to end-organ damage. It's classified into typical HUS (caused by Shiga toxin-producing E. coli), atypical HUS (due to uncontrolled complement activation), and secondary HUS (sHUS) linked with coexisting conditions. We present a compelling case of a 21-year-old female with fever, jaundice, anemia, thrombocytopenia, and oliguric acute kidney injury (AKI), ultimately diagnosed with Plasmodium vivax malaria. Despite adequate antimalarial therapy, the patient's clinical trajectory remained intricate, characterized by sustained hematological abnormalities and renal dysfunction. A comprehensive assessment revealed Coombs-negative hemolytic anemia. Subsequently, a renal biopsy confirmed TMA. Considering the rarity of vivax malaria causing TMA, an autoimmune workup was conducted, suggesting systemic lupus erythematosus (SLE). Systemic autoimmune disease-associated HUS (SAID-HUS) is a rare entity that exhibits diverse clinical presentations, with SLE being best-described etiology in literature. SLE-associated HUS was considered and was managed with steroids and hydroxychloroquine resulting in significant renal and hematological improvement. This report underscores significance of assessing autoimmune factors in case of secondary TMA, while also shedding light on evolving understanding of vivax malaria's potential relationship with TMA.